Переосмислюючи Центрально-Східну Європу - Волошин, Ю. (Соціум. Альманах соціальної історії, 2017)
Рецензія на книгу: Mikołaj Szołtysek. Rethinking East-Central Europe: family systems and co-residence in the Polish-Lithuanian Commonwealth. Volume 1: Contexts and analyses; Volume 2: Data quality assessments, documentation, and bibliography. – Bern, Berlin, Bruxelles, Frankfurt am Main, New York, Wien: Peter Lang, 2015. – 1066 pp.. - C. 373.